Efficacy of Oral Doxycycline in Reducing the Size of Pterygium lesions - Rabbani, Shafaq; Akram, Amjad; Yaqub, Amer; Ashraf, Ammara; Khan, Fatima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the efficacy of oral Doxycycline in reducing the size of pterygium lesions in a Pakistani populationStudy Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, from Sep 2018 and May 2019.Methodology: Sixty patients above 20 years of age were enrolled in the study. Oral Doxycycline 200m/day was given for thirty consecutive days. Photographs of the lesions were taken at the time of recruitment and at the end of the study for assessment of pterygium size. Difference between pre-treatment and post-treatment size was analysed and comparison was made with age, gender and initial lesion size.Results: Twenty-two females and thirty-eight males were examined. The mean age of the participants was 48.8 ± 13.8 years. The mean size of the pterygium lesions before commencing the treatment was 12.24 ± 6.28 mm2. The mean size of the lesions after the treatment was 11.24 ± 5.39 mm2. The mean difference size was 1.00 ± 1.62 mm2 (p